Pemanfaatan sumber energi panas bumi untuk pengeringan ikan di Desa Idamdehe Kabupaten Halmahera Barat Provinsi Maluku Utara - Abdurrachman Baksir; Kadri Daud; Eko S Wibowo; Nebuchadnezzar Akbar; Irfan Haji (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Due to the location at the ring of fire, Indonesia has 252 geothermal potentials distributed in various regions, from Java to Nusa Tenggara, together with Sulawesi and Maluku. Geothermal points are found in North Maluku in Idamdehe Village, West Halmahera. Research on the usage of geothermal energy for fish processing in Indonesia, especially North Maluku, is very limited. Therefore, this study was aimed to use geothermal energy for fish processing using a modified oven. The sample used was the yellowstripe scad (Selaroides leptolepis). In situ measurement was done to obtain the geothermal steam temperature which is 70°C to 130°C. The experiments wewe done in 4 hours for the fish drying processed with three sets of temperature including 0°C, 50°C and 100°C. The results suggest geothermal as a promising energy souce for fish processing.